Politician's dilemma : building state capacity in Latin America - Geddes, Barbara (University of California Press, 1994)
In Latin America as elsewhere, politicians routinely face a painful dilemma: whether to use state resources for national purposes, especially those that foster economic development, or to channel resources to people and projects that will help insure political survival and reelection. While politicians may believe that a competent state bureaucracy is intrinsic to the national good, political realities invariably tempt leaders to reward powerful clients and constituents, undermining long-term competence. Politician's Dilemma explores the ways in which political actors deal with these contradictory pressures and asks the question: when will leaders support reforms that increase state capacity and that establish a more meritocratic and technically competent bureaucracy? Barbara Geddes brings rational choice theory to her study of Brazil between 1930 and 1964 and shows how state agencies are made more effective when they are protected from partisan pressures and operate through merit-based recruitment and promotion strategies. Looking at administrative reform movements in other Latin American democracies, she traces the incentives offered politicians to either help or hinder the process. In its balanced insight, wealth of detail, and analytical rigor, Politician's Dilemma provides a powerful key to understanding the conflicts inherent in Latin American politics, and to unlocking possibilities for real political change.
Keywords: Latin America -- Politics and government -- 20th century.; Bureaucracy -- Latin America -- History -- 20th century.; Civil service reform -- Latin America -- History -- 20th century.; Amérique latine -- Politique et gouvernement -- 20e siècle.; Bureaucratie -- Amérique latine -- Histoire -- 20e siècle.; Fonction publique -- Réforme -- Amérique latine -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Public Affairs & Administration.; POLITICAL SCIENCE -- Government -- Executive Branch.; HISTORY / Latin America / General; Bureaucracy; Civil service reform; Politics and government; Latin America; Politisches System; Verwaltungsreform; Lateinamerika; Politica (america latina); Burocracia.; 1900-1999; administrative reform movements.; analytical.; channel resources to people and projects.; detailed.; insure political survival and reelection.; latin american politics.; political actors and contradictory pressures.; possibilities for real political change.; rational choice theory.; state resources for national purposes.; study of politics in brazil.; History